PROBLEMATIKA DAN PERLINDUNGAN HUKUM TERHADAP BURUH MIGRAN PEREMPUAN DAN PADA MASA PANDEMI COVID-19 - SITI HAJAR (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
This article is focused to explain many problems and how to protect Indonesia’s employees migran care in the era of pandemic covid-19. In the era pandemic covid-19, media has signifcant role in all aspects of life, included role to protect Indonesian’s employee and labor of migrant.Technological innovation of computer and internet has facilitates communication among member of labor migrant and Indonesia’s employee, and fastened information